Serum fetuin-a and risk of thoracic aortic aneurysms: a two-sample mendelian randomization study - Chen, Yang; Zhu, Jiayi; Guo, Xin; Cao, Chenghui; Xiao, Xuan; Zhu, Botao; Weng, Shuwei; Hu, Die; Luo, Yonghong; Wang, Shuai; Wu, Sha; He, Jia; et al. (Frontiers in Endocrinology, 2024)
Background: Recent studies have revealed a significant decrease in serum fetuin-A levels in atherosclerotic aneurysms, indicating that fetuin-A may play a protective role in the progression of arterial calcification. However, the specific mechanism behind this phenomenon remains unclear. We aimed to examine the association between fetuin-A levels in thoracic aortic aneurysms (TAAs) and risk of TAAs and to evaluate whether this association was causal. Methods: A total of 26 SNPs were selected as instrumental variables for fetuin-A in 9,055 participants of European ancestry from the CHARGE consortium, and their effects on thoracic aortic aneurysm and decreased descending thoracic aortic diameter were separately estimated in 353,049 and 39,688 individuals from FinnGen consortium. We used two-sample Mendelian randomization (MR) analysis to examine the causal association. At the same time, we employed various methods, including random-effects inverse variance weighting, weighted median, MR Egger regression, and MR PRESSO, to ensure the robustness of causal effects. We assessed heterogeneity using Cochran's Q value and examined horizontal pleiotropy through MR Egger regression and retention analysis. Results: Fetuin-A level was associated with a significantly decreasing risk of thoracic aortic aneurysm (odds ratio (OR) 0.64, 95% CI 0.47 - 0.87, P = 0.0044). Genetically predicted fetuin-A was also correlated with the decreased descending thoracic aortic diameter (β = -0.086, standard error (SE) 0.036, P = 0.017). Conclusions: Serum fetuin-A level was negatively associated with risk of TTA and correlated with the decreased descending thoracic aortic diameter. Mendelian randomization provides support for the potential causal relationship between fetuin-A and thoracic aortic aneurysm.